Alteration of Tear Cytokine Expressions in Primary Acquired Nasolacrimal Duct Obstruction – Potential Insights into the Etiopathogenesis. (2nd April 2020) - Ali, Mohammad Javed; Patnaik, Satish; Kelkar, Natasha; Ali, Mohammad Hasnat; Kaur, Inderjeet
ABSTRACT: Purpose : To investigate the presence and level of 35 distinct cytokines in the tear fluid obtained from patients with primary acquired nasolacrimal duct obstruction (PANDO) and compare it with controls in an effort to understand the disease etiopathogenesis. Methods : Standard protocols were used for collecting tears from 60 eyes (20 diseased eyes and 20 healthy fellow eyes of unilateral PANDO, 20 control eyes of healthy subjects). A total of 35 analytes involved in inflammation, angiogenesis and wound healing were assessed by multiplex ELISA. Alterations in the tear levels of cytokines in PANDO and their comparison with the levels in the non-diseased fellow eye and healthy volunteers were noted. STRING analysis was used to assess the involved biological pathways of the altered cytokines. Linear mixed effect model was used for statistical analysis. A P value of <0.05 was considered significant. Results : There was significant upregulation of 10 pro-inflammatory cytokines in tears from diseased eyes of PANDO patients in comparison with the non-diseased controls and include matrix metalloproteinase 9 (MMP 9), serpin E1, Interleukin-6 (IL-6), hepatocyte growth factor (HGF), vascular endothelial growth factor-A and R2 (VEGF-A, VEGF R2), platelet-endothelial cell adhesion molecule (PECAM-1), c-reactive protein (CRP), chemokine ligand 2 (CCL2) and platelet-derived growth factor- AA (PDGF-AA). Amongst the anti-inflammatory cytokines, three were significantly upregulated in diseased eyes of PANDO patients in comparison with the non-diseased controls and include granulocyte-colony stimulating factor (G-CSF), retinol binding protein 4 (RBP4) and tissue inhibitor of metalloproteinases −1 (TIMP-1). There were no significant differences between the control eyes of the diseased patient and control eyes of healthy subjects. Based on the significantly altered cytokines, string analysis revealed that the biological pathways involved in the etiopathogenesis of PANDO include inflammation, angiogenesis, negative regulation of apoptosis, cellular proliferation and hormonal regulation. Conclusions : In cases of PANDO, dysregulation of certain cytokines was disease specific. Biological pathways reflect a possible link and interaction between the inflammatory cytokines with vasculature and hormonal microenvironments of the lacrimal drainage system, which in a way is bringing three promising candidates in the PANDO etiopathogenesis on a common ground.